Inovasi Pembelajaran Bahasa Inggris: Penggunaan Boneka dalam Kegiatan Storytelling dengan tekhnik ventriloquist untuk Siswa SD - Wulandari, Fitri; Suyono, Akhmad; Sari, Cyntia Kumala; Marhamah; Suryanti , Nunuk (Community Education Engagement Journal, 2025)
This community service project aims to introduce an innovative approach to enhancing English learning motivation at SDN 02 Tualang, through storytelling using ventriloquist techniques with hand puppets. The ventriloquist technique involves using the diaphragm to produce speech while animating hand puppets that possess distinct character personalities to narrate stories in English. This storytelling method can create an engaging learning atmosphere, encourage student participation, and improve students' speaking skills and confidence. This community service project was conducted at SDN 02 Tualang in Siak Regency, involving 200 students from grades 1 to 4. The results of the project indicate that storytelling using ventriloquist techniques positively impacts students' motivation to learn English.